(untitled) (Journal of Partial Differential Equations, 2021)
"In this paper, we discuss the local existence of weak solutions for a parabolic system modelling chemotaxis with memory term, and we show the finite-time blow-up and chemotactic collapse for this system. The main methods we used are the fixed point theorem and the semigroup theory."